ASSESSING THE IMPACT OF SOCIAL WELFARE ON INCOME INEQUALITY AND SUSTAINABLE ECONOMIC DEVELOPMENT IN THE EUROPEAN UNION - MECA ALINA; ZLATI MONICA LAURA; VALENTIN-MARIAN ANTOHI; COSTINELA FORTEA (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Income inequality is a major challenge for the European Union, with significant implications for economic sustainability, social stability and cohesion between Member States. This study aims to analyse the impact of economic and social factors on income distribution in the EU, using the GINI coefficient as the dependent variable. Given the importance of public policies in reducing economic disparities, the research investigates the relationships between economic growth, employment, education, poverty and social protection on income inequality over the period 2014 2023. The methodology used is based on a generalized linear regression model estimated using Eurostat data to determine the influence of each variable on income distribution. The results suggest that economic expansion contributes to reducing inequality. Also, the at-risk-of-poverty rate positively influences income inequality, reflecting the limited effectiveness of social protection mechanisms. In addition, employment does not automatically reduce inequality, being influenced by job insecurity and wage differentials. Based on these findings, the study recommends a number of European public policies, including increased investment in education and lifelong learning, improving the efficiency of social transfers, implementing progressive tax policies and stimulating employment in productive sectors. The results are useful for economic and social policy makers in the European Union, informing the formulation of effective strategies to reduce income inequality and promote inclusive growth.